Nasolabial and forehead flap reconstruction of contiguous alar–upper lip defects. Issue 3 (March 2017) - Zelken, Jonathan A.; Reddy, Sashank K.; Chang, Chun-Shin; Chuang, Shiow-Shuh; Chang, Cheng-Jen; Chen, Hung-Chang; Hsiao, Yen-Chang
Summary: Background: Defects of the nasal ala and upper lip aesthetic subunits can be challenging to reconstruct when they occur in isolation. When defects incorporate both the subunits, the challenge is compounded as subunit boundaries also require reconstruction, and local soft tissue reservoirs alone may provide inadequate coverage. In such cases, we used nasolabial flaps for upper lip reconstruction and a forehead flap for alar reconstruction. Methods: Three men and three women aged 21–79 years (average, 55 years) were treated for defects of the nasal ala and upper lip that resulted from cancer (n = 4) and trauma (n = 2). Unaffected contralateral subunits dictated the flap design. The upper lip subunit was excised and replaced with a nasolabial flap. The flap, depending on the contralateral reference, determined accurate alar base position. A forehead flap resurfaced or replaced the nasal ala. Autologous cartilage was used in every case to fortify the forehead flap reconstruction. Results: Patients were followed for 25.6 months (range, 1–4 years). All the flaps survived, and there were no complications. Satisfactory aesthetic results were achieved in every case. With the exception of a small vertical cheek scar and a vertical forehead scar, all incisions were concealed within the subunit borders. Conclusion: From preliminary experience, we advocate combining nasolabial flap reconstruction of the upper lip with a forehead flap reconstruction of the ala to preserve normal facial appearance. This combination addresses an important void in the algorithmic approach to central facial reconstruction.